2012
DOI: 10.1080/0144929x.2011.642893
|View full text |Cite
|
Sign up to set email alerts
|

What should a corporate website look like? The influence of Gestalt principles and visualisation in website design on the degree of acceptance and recommendation

Abstract: Internet users decide within seconds, whether to elaborate on a website, or to go on to a new page. This calls for investigation of the factors influencing this decision. In two studies, we presented websites for 3 s and analysed the effect implementation of Gestalt principles (GPs) and visualisation of an interaction partner has on acceptance, recommendation of the site by the user, and social presence. Study 1 implemented a 3 (Gestalt principle of proximity: no, medium and strong implementation) 6 3 (Gestalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…This argument is in line with the viewpoint that a simple layout can be processed more fluently [11], [13].…”
Section: A Visual Design Principlessupporting
confidence: 57%
See 2 more Smart Citations
“…This argument is in line with the viewpoint that a simple layout can be processed more fluently [11], [13].…”
Section: A Visual Design Principlessupporting
confidence: 57%
“…Literature has suggested that an environment which is organized by arranging related elements together will present a clearer and cleaner view that aids in recognizing those elements with ease [4], [12] and facilitates the information processing [13]. Liu and Ma [32] also stressed that users can locate the information they want faster by making different parts of the website interface discernible through arrangement.…”
Section: Classical Aesthetics and Learning Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…The qualities of experimental stimuli in the analyzed studies are unclear, because most of them did not include the stimuli in the reports. In the case that a study included the stimuli (e.g., Möller et al, 2012), however, the qualities of drawing are not as good and clear as those of photographs. Of course, this speculation, the persuasive quality difference between different types of visual images, needs further investigation, but still the moderator analysis presents an obvious, but important idea on visual persuasion: All images do not equally produced to enhance persuasion, and their qualities must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Gestalt theory has been utilized to study aspects of mobile application usability (see for example Paay and Kjeldskov, 2007) as they have proven to be highly effective in the context of traditional desktop and website applications (Moller et al, 2012). Gestalt theory includes several gestalt laws (e.g., proximity of objects) and explains how humans perceive objects in their environment and how they form such perceptions (Wertheimer and Riezler, 1944).…”
Section: Gestaltmentioning
confidence: 99%